The certainty of a few good reactions - Moorhouse, Adam D.; Homer, Joshua A.; Moses, John E. (Chem, 2023)
The impact of click chemistry was recently recognized with the 2022 Nobel Prize in Chemistry. The breadth of areas where click chemistry has accelerated discovery is extensive. In one of the most written-about subjects in Chemistry over recent years, this short perspective zones in on a small fragment of what we consider to be some of the most critical developments in synthetic chemistry, which have expanded access to the click chemistry toolbox. In addition, we touch upon areas within medicinal chemistry and novel approaches to drug discovery enabled by click chemistry, where we believe there is untapped potential for biological functions to be found and exploited. [Display omitted] Challenges and opportunities:•Click chemistry drives unrivaled opportunities for creating functional molecules. We look to an exciting future where discovery and process chemistry merge; that is, where click reactions and associated functional molecules find mass-market deployment. However, this will largely depend on the availability and accessibility of suitable screens, the development of new assays, and further innovation to ensure that the desirable properties from the myriad of candidate molecules generated by click chemistry are realized.•Numerous developments, such as click-activated drugs, inverse drug discovery, and “sleeping beauty” probes, have the potential to form platform technologies. No doubt, other yet-to-be-discovered methods for drug discovery and chemical biology will change the direction of these endeavors.•As the application of artificial intelligence in chemistry makes gains, we advocate a case for click chemistry principles to expedite the realization of in silico discoveries. The 2022 Nobel Prize in Chemistry was the crowning glory for the already vindicated field of click chemistry. At its heart, the click approach toward discovering functional molecules relies upon the dependability of a core family of privileged chemical reactions. Focusing on what we believe are significant developments that enrich the click chemistry toolbox from the perspective of medicinal chemistry, we hope this account inspires the search for new functions and click chemistries.